2006
DOI: 10.1097/01.rhu.0000249770.86652.3b
|View full text |Cite
|
Sign up to set email alerts
|

Sphygmomanometry-Evoked Allodynia???A Simple Bedside Test Indicative of Fibromyalgia

Abstract: In this developmental study of patients attending rheumatology clinics, the generation of pain during blood pressure testing was strongly associated with the diagnosis of FM. This robust linkage probably reflects a tautologic phenomenon. A sine qua nonelement for FM diagnosis is the presence of tender points in discrete anatomic sites. These tender points in turn reflect a state of generalized mechanical allodynia that can be locally elicited by the cuff pressure during blood pressure testing. Sphygmomanometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 6 publications
4
25
0
Order By: Relevance
“…Patients were identified based on both their responses to a screening survey for CWP (bilateral pain, above/below waist lasting ≥ 1 week in the past 3 months), according to the 4 pain questions of the London Fibromyalgia Epidemiology Study Screening Questionnaire (LFESSQ-4; Table 1 ) [28], and a site visit for physician evaluation of fibromyalgia. During the site visit, physicians completed a tender point exam [29] and blood pressure cuff exam [30], and patients completed the EuroQol 5 dimensions (EQ-5D; Table 1 ) [31]. Physicians at the study sites had completed FM diagnostic training and reported treating at least 10 FM patients on average each month in their practice.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Patients were identified based on both their responses to a screening survey for CWP (bilateral pain, above/below waist lasting ≥ 1 week in the past 3 months), according to the 4 pain questions of the London Fibromyalgia Epidemiology Study Screening Questionnaire (LFESSQ-4; Table 1 ) [28], and a site visit for physician evaluation of fibromyalgia. During the site visit, physicians completed a tender point exam [29] and blood pressure cuff exam [30], and patients completed the EuroQol 5 dimensions (EQ-5D; Table 1 ) [31]. Physicians at the study sites had completed FM diagnostic training and reported treating at least 10 FM patients on average each month in their practice.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It has been recommended that the blood pressure cuff be inflated at an approximate rate of 10 mm Hg per second up to 180 mm Hg or to the point at which pain is elicited. Healthy persons usually experience pain when the blood pressure cuff is inflated to 160 mm Hg or more; patients with FM, though, usually experience pain at 100 to 110 mm Hg, or even with less pressure [23]. …”
Section: Methodsmentioning
confidence: 99%
“…15 The presence of allodynia was also assessed with a sphygmomanometer following the previously published protocol. 16 Blood pressure cuff is inflated at the rate of 10 mm Hg per second up to 180 mm Hg. The following question is asked to the patient: ''Tell me if the cuff's pressure brings forth pain.''…”
Section: Methodsmentioning
confidence: 99%